Meningkatkan Kemampuan Sains dengan Metode Eksperimen Mencampur Warna di KB Widya Purwacaraka Pati - Ana Reknowati; Sumiyati Sumiyati (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2017)
The purposes of this research is to know: (1) The ability of children's science in KB Widya Purwacaraka Cabak, and (2) the effect of the experimental method of mixing the color to children's science skills in KB Widya Purwacaraka Cabak. This type of research includes Classroom Action Research. The results of the study concluded that: (1) The ability of children's science in KB Widya Purwacaraka Cabak Pati before the action is still low. The level of children's science skills that are included in the category of Emerging (MM) and Not Emerging (BM) is 64.52%. (2) The use of mixed color experimental methods can improve children's science skill. This is shown from: (a) Increasing the ability of children science including Very Good Developing (BSB) and Expectancy Developing (BSH) from the pre cycle, cycle I and cycle II, that is pre new cycle of 35,48%, cycle I become 67.74% and cycle II increased again to 93.55%. (2) Increasing the average score of children's science skills from pre cycle, cycle I and cycle II, that is pre-cycle 2 which belongs to the Emerging (MM) category, cycle I increases to 3 which belongs to Expectancy Developing (BSH) category, and cycle II the average score increased again to 3 and included the category Expectancy Developing (BSH).